2013
DOI: 10.1590/s0034-737x2013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Produção de matéria seca da braquiária de acordo com os atributos químicos de um Latossolo em Selvíria, Mato Grosso do Sul

Abstract: Dry matter production of braquiaria due to the chemical properties of an oxisol in Selvíria, Mato Grosso do Sul, BrazilRustic forages as the signal-grass are predominant in areas of Cerrado in extensive livestock systems that favor soil degradation. However, with time, not even these forages can have a good development in those areas. The objective of this study was to analyze the variability of plant and soil attributes; to define the linear and spatial correlations between signal-grass yield and the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
4
7
3
1
Order By: Relevance
“…Already Martins et al (2009), when analyzing a dystroferric Red Latosol under no-tillage, in regular grids of 135 sampling points, found high variability (24%) for grain yield in common bean. In this respect, it differed from those obtained by Megda et al (2008) and Montanari et al (2013b), who found values of medium variability (19, 18.3%) in a dystroferric Red Latosol under no-tillage. The traits NG, NP and DM presented high variability, with coefficients of variation of 26.5; 21.1 and 24.3%, respectively.…”
Section: Resultscontrasting
confidence: 95%
See 3 more Smart Citations
“…Already Martins et al (2009), when analyzing a dystroferric Red Latosol under no-tillage, in regular grids of 135 sampling points, found high variability (24%) for grain yield in common bean. In this respect, it differed from those obtained by Megda et al (2008) and Montanari et al (2013b), who found values of medium variability (19, 18.3%) in a dystroferric Red Latosol under no-tillage. The traits NG, NP and DM presented high variability, with coefficients of variation of 26.5; 21.1 and 24.3%, respectively.…”
Section: Resultscontrasting
confidence: 95%
“…Geostatistical analysis (Table 3) showed that there was a spatial dependence for the semivariograms of the phenological indices YIE, MHG and DM, which adjusted to the spherical model, whereas SD adjusted to the exponential model, agreeing with Montanari et al, (2013b), who reported that spherical and exponential models are the most common theorists of soil and plant attributes. However, phenological indices NG, NGP, NP and PL adjusted to the Gaussian model.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…A resposta das plantas forrageiras à irrigação e adubação nitrogenada varia conforme o potencial genético das gramíneas (MAGALHÃES et al, 2012) e a boa qualidade do solo é fator determinante da produtividade de matéria seca elevada (MONTANARI et al, 2013). Independente da produção de biomassa, a relação folha:colmo para todos os tratamentos foi estatisticamente igual, sendo 2,4:1, 2,0:1, 2,8:1, 3,0:1 e 2,3:1 para os tratamentos 0N0K, 150N120K, 300N240K, 450N360K e 600N480K, respectivamente.…”
Section: Resultado E Discussãounclassified